Traditional Knowledge on Ethno-medicinal Uses Prevailing in Tribal Pockets of Harda and Raisen Districts of Madhya Pradesh - Nath, V.; Khatri, P. K. (Indian Forester, 2011)
The present paper deals with the traditional knowledge gathered on medicinal plants used against various diseases from traditional herbal healers of Harda and Raisen districts of Madhya Pradesh, India. Information collected from the traditional healers locally known as Vaidhya/Ojha has revealed that plant/plant parts of 37 species from Harda district and 60 species from Raisen district of forest origin are being utilized as paste, powder, juice, decoction and extract for the treatment of various human diseases. Habit and utilization of plants and the percentage of different formulation of herbal medicine being prepared by the herbal healers of the study area have also been documented.